Vinyl, album, cover, art the complete Hipgnosis catalogue - Powell, Aubrey (Thames & Hudson, 2017)
The complete, definitive and never-before-published catalogue of Hipgnosis, Vinyl * Album * Cover * Art finally does justice to the work of the most important design collective in music history, which, according to Roddy Bogawa, director of the documentary Taken by Storm (2011), 'designed half your record collection'. Founded in 1967 by Storm Thorgerson, Aubrey 'Po' Powell and Peter Christopherson, Hipgnosis gained legendary status in graphic design, transforming the look of album art forever and winning five Grammy nominations for package design. Their revolutionary cover art moved away from the conventional group shots favoured by record companies of the day, resulting in the ground-breaking, often surreal designs which define the albums of many of the biggest names in the history of popular music: 10cc, AC/DC, Black Sabbath, Peter Gabriel, The Police, Genesis, Led Zeppelin, Pink Floyd, Paul McCartney, Robert Plant, Syd Barrett, Throbbing Gristle
Includes index
Keywords: Thorgerson, Storm -- 1944-2013; Geschichte 1900-2000; Geschichte; Cover; Grafikdesign; Schallplatte; Hipgnosis (Design studio) / History; Graphic arts; Sound recordings / Album covers / Catalogs; Graphic arts / England / History / 20th century; Katalog; Werkverzeichnis